The Sooner the Better: High-Value Care Education in Medical School. (November 2019) - Erath, Alexandra; Mitchell, Margaret; Salwi, Sanjana; Liu, Yangzi; Sherry, Alexander
Abstract : Over the last decade in the United States, a national emphasis on controlling health care costs has prompted the medical community to embrace the ideal of high-value care (HVC), with value defined as health outcomes achieved per dollar spent. Despite increasing recognition of its importance as a skill for the modern physician, the practice of HVC remains a relatively new concept. Integrating HVC into medical education has been heterogeneous at best, with the majority of current HVC education thus far implemented at the postgraduate level. The authors present the unique benefits of the earlier introduction of HVC training at the medical school level, including ease of standardization across programs, a synergy in learning the value of an intervention alongside its other innate qualities, and the establishment of a foundational HVC education to allow for specialty-specific value training during residency. In this Invited Commentary, the authors offer practical recommendations for the incorporation of HVC training into medical schools' curricula, with special attention to correlating specific education strategies with the preclerkship, clerkship, and elective years of medical school.